2011
DOI: 10.1111/j.1447-0756.2010.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot randomized trial for treatment of bacterial vaginosis using in situ forming metronidazole vaginal gel

Abstract: Pilot testing showed that in situ MTZ vaginal gel is more effective than the conventional vaginal gel for long-term cure of BV. These findings suggest a novel and efficient long-term treatment of BV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…One group in Egypt working on pluronic polymers, has developed a hydrogel that swells in aqueous environments for use as a drug delivery system. This novel vaginal delivery system for metronidazole, improved the therapeutic efficacy compared with that achieved with conventional vaginal gel 62. In a pilot randomized trial, while similar cure rates were reported after 1 week of treatment (85% in the new vaginal gel group and 71.4% in the conventional vaginal gel group; P = 0.294), the cure rate was significantly higher after 4 weeks in the new gel group compared with the conventional gel group (80% and 47%, respectively).…”
Section: Emerging Therapiesmentioning
confidence: 97%
“…One group in Egypt working on pluronic polymers, has developed a hydrogel that swells in aqueous environments for use as a drug delivery system. This novel vaginal delivery system for metronidazole, improved the therapeutic efficacy compared with that achieved with conventional vaginal gel 62. In a pilot randomized trial, while similar cure rates were reported after 1 week of treatment (85% in the new vaginal gel group and 71.4% in the conventional vaginal gel group; P = 0.294), the cure rate was significantly higher after 4 weeks in the new gel group compared with the conventional gel group (80% and 47%, respectively).…”
Section: Emerging Therapiesmentioning
confidence: 97%
“…Clinical evaluation of formula F 7 in comparison with the marketed preparation (Tricho ® gel) in patients with bacterial vaginosis (20) showed that the cure rate after one week of treatment was 85 % in the in situ gel F 7 group and 71 % in the conventional vaginal gel group (Tricho ® gel), while after 4 weeks, the cure rate showed a significant difference in the in situ gel group compared to the conventional vaginal gel group (80 versus 47 %, respectively, p = 0.034). This shows that the in situ MTZ vaginal gel F 7 is more effective than the conventional vaginal gel product for sustained cure of bacterial vaginosis.…”
Section: Comparison Of Mtz Release From the Selected In Situ Gelling mentioning
confidence: 99%
“…Clinical study: improved efficacy after a 5 day treatment (twice daily app.) with significant difference in cure rate after 4 weeks versus Tricho ® Tgel (28ºC) [155,156].…”
Section: Microscopic Featuresmentioning
confidence: 93%